Cognitive processes underlying reading and naming deficits in dyslexic readers - Araújo, Susana (2014)
In addition to phonological deficits, difficulties at the level of the visual recognition system (i. e. , the mechanisms that could affect the induction of orthographic representations or the connection of visual to lexical codes) constitute potential sources of the poor reading and visual naming that characterize dyslexia.